An investigation of trachoma vaccine regimens by the chlamydia vaccine CTH522 administered with cationic liposomes in healthy adults (CHLM-02): a phase 1, double-blind trial - Pollock, KM; Borges, AH; Cheeseman, HM; Rosenkrands, I; Schmidt, KL; Søndergaard, RE; Day, S; Evans, A; McFarlane, LR; Joypooranachandran, J; Amini, F; Skallerup, P; et al. (Elsevier, 2024)
Background There is no vaccine against the major global pathogen Chlamydia trachomatis; its different serovars cause trachoma in the eye or chlamydia in the genital tract. We did a clinical trial administering CTH522, a recombinant version of the C trachomatis major outer membrane molecule, in different dose concentrations with and without adjuvant, to establish its safety and immunogenicity when administered intramuscularly, intradermally, and topically into the eye, in prime-boost regimens.